KOMPETENSI PENDIDIK DALAM PERSPEKTIF M. NATSIR (Studi Analitis Pemikiran Pendidikan M. Natsir dalam â€œFiqhud Dakwahâ€) - Maulida, Ali (Universitas Islam Sultan Agung, 2018)
The real preacing is educating human being to change into positif direction. As a teacher and an educator for the nation, M. Natsir has understood well his nation character and the character of preaching that is very complext. He is concern to the effort of giving training for teachers. He reads, thinks and reflects the Qurâ€™an and Hadits and the path way of the Prophets Muhammadâ€™s struggle and his close friends as the first generation this umah in spreading an Islamic teaching, then the result of his reflection is written in his various master piece such as: Fiqhud Daâ€™wah. This research is a library research, in which the researcher has conducted research, analysis, reading Fiqhud Daâ€™wah book and relevant literatur in accordance with the topic of reseach. Related to the concept of teacherâ€™s competences who has a role as educator. From this research, it can be drawn a conclusion that the perspective of M. Natsir related to the teacherâ€™s competences is very comprehensive, for example: teacher has to pay an attention to his qualification such as: 1) guiding the soul (al-Iâ€™dad al-Fikry); 2)preparation in the knowleadge and science; and 3) caring about â€œakhlaqâ€™. The Islamic studies teacher has not only Islamic studies knowledge, broaden paradigm, and understading the characters of his/ her society. They are not only demanded to be a teacher educated and guided with the sincere heart, but they is also a role model who direct his/her â€œummahâ€ by applying an honour â€œakhlakâ€ to themselvesKeywords: preacing, teacherâ€™s competences, preacing characteristic